Nitrogen utilization analysis reveals the synergetic effect of arginine and urea in promoting fucoxanthin biosynthesis in the mixotrophic marine diatom Phaeodactylum tricornutum - Yang, Runqing; Wei, Dong; Pohnert, Georg (Frontiers in Marine Science, 2022)
Fucoxanthin is a new dietary ingredient applied in healthy food with specific benefits of body-weight loss and liver fat reduction. The marine diatom Phaeodactylum tricornutum is a highly suitable species for fucoxanthin production. In the present study, aiming to promote fucoxanthin biosynthesis in mixotrophic P. tricornutum, NaNO3, tryptone and urea were evaluated as nitrogen sources with 0.10 mol L-1 glycerol as organic carbon source for mixotrophic growth in shake flasks. Compared to NaNO3, the mixture of tryptone and urea (referred as T + U, 1:1, mol N: mol N) as organic nitrogen sources could induce a higher biomass and fucoxanthin production. Through nitrogen utilization analysis, leucine, arginine, lysine, and phenylalanine in T+U medium were identified as the amino acids that primarily support cell growth. Among those amino acids, arginine causes the highest rate of nitrogen utilization and cell growth promotion. After 12-days cultivation, the highest biomass concentration (3.18 g L-1), fucoxanthin content (12.17 mg g-1) and productivity (2.68 mg L-1 d-1) were achieved using 25 mmol N L-1 arginine and 5 mmol N L-1 urea as nitrogen source, indicating that arginine and urea performed synergistically on enhancing biomass and pigments production. This study provides new insight into the promotion of fucoxanthin biosynthesis by nitrogen utilization analysis and verifies the synergetic effect of arginine and urea on facilitating the development of a promising strategy for efficient enhancement of fucoxanthin production through mixotrophic cultivation of P. tricornutum.